Daily intake of heat-killed Lactobacillus plantarum L-137 enhances type I interferon production in healthy humans and pigs - Arimori, Yojiro; Nakamura, Risa; Hirose, Yoshitaka; Murosaki, Shinji; Yamamoto, Yoshihiro; Shidara, Osamu; Ichikawa, Hiroshi; Yoshikai, Yasunobu (Immunopharmacology and immunotoxicology, 2012)
We have previously reported that oral administration of heat-killed Lactobacillus plantarum L-137 (HK L-137) stimulates innate immunity for production of type I interferon (IFN) which subsequently augments host defense against influenza A virus infection in mice. We here examined the effect of HK L-137 intake on type I IFN in humans. Sixteen subjects were randomly assigned to receive a tablet containing 10 mg of HK L-137 or a matching tablet for 8 weeks and the serum levels of type I IFN were examined before and after the first or second dose of the trivalent inactivated influenza vaccine. There were no differences in the seroresponse rate, the seroprotection rate and the geometric mean Ab titers after either the first or second dose of vaccine between the HK L-137 group and the control group. On the other hand, the levels of IFN-β were significantly higher in the HK L-137 group than in the control group before vaccination although the vaccination conferred little additional induction of IFN-β. We further examined IFN-β gene expression in the whole blood cells of pigs fed on a diet containing HK L-137 and found that the IFN-β mRNA levels were significantly higher in the HK L-137 group than in the control group. The finding that daily intake of HK L-137 enhances type I IFN production and host defense against influenza A virus infection in mice may be applied to at least two additional species.